2009
DOI: 10.1038/modpathol.2008.151
|View full text |Cite
|
Sign up to set email alerts
|

D2-40 in breast cancer: should we detect more vascular emboli?

Abstract: Peritumoral emboli assessed on hematoxylin-eosin-stained slides are taken into account for treatment of patients with operable breast cancer. We assessed whether immunostaining with D2-40 improves the prognostic significance of emboli in a group of tumors with a large immunohistochemical sampling and a longterm follow-up. Topography, number, and extension of hematoxylin-eosin and D2-40 emboli were compared in 94 node-negative breast cancers (median number of immunostained slides per tumor: 3). Metastatasis-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…LVI was assessed on HE stained slides, as defined by Rosen and Oberman7. Tumour cell emboli within endothelium-lined vascular spaces are seen on HE stained slides of the breast cancer8.…”
Section: Methodsmentioning
confidence: 99%
“…LVI was assessed on HE stained slides, as defined by Rosen and Oberman7. Tumour cell emboli within endothelium-lined vascular spaces are seen on HE stained slides of the breast cancer8.…”
Section: Methodsmentioning
confidence: 99%
“…10,11 In a previous work on lymph node-negative tumors, we also observed that D2-40 increases the diagnostic sensitivity of LVI by a factor of 1.4, and strengthens the prognostic impact of this factor. 9 As only peritumoral LVI has prognostic significance, this analysis cannot be easily performed on tissue microarray blocks. It may be anticipated that such complementary analysis would also give similar results in lymph node-positive tumors.…”
Section: Discussionmentioning
confidence: 99%
“…1), in the breast surrounding invasive carcinoma, that is, separated from the tumor by normal breast tissue and often next to a small artery or vein. 1,8,9 When H & E LVI was suspected in the vicinity of the tumor, differential diagnosis with an artifact (retraction) was difficult, and such equivocal cases were recorded as negative. In our study, only unequivocal H & E LVI was prospectively recorded as positive without distinguishing blood vessels from lymphatics.…”
Section: Definition Of Lymphovascular Invasionmentioning
confidence: 99%
“…Lymphovascular invasion (LVI) is defined as tumor emboli present within a definite endothelial-lined space in the breast surrounding invasive carcinoma [6,7]. The existence of LVI may help identify who is at increased risk for axillary lymph node and distant metastasis [2,3] Although LVI has been accepted as an important prognostic factor in patients with lymph node-negative invasive breast cancer [8], LVI is controversial regarding prognostic value in patients with lymph node-positive breast cancer [3,9-11].…”
Section: Introductionmentioning
confidence: 99%